Mens Rea Analysis in Fraud Upcoding of BPJS Kesehatan Claims by Hospitals - Muttia A. Sutja; Teguh Wijayanto; Tjut Ika Harita Hayu; Tri Budiastuti; Ateng Karsoma (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The National Health Insurance (Jaminan Kesehatan Nasional [JKN]) claim system, managed by BPJS Kesehatan, faces increasing fraud risks, particularly through upcoding—the deliberate manipulation of diagnosis or procedure codes to inflate claim values. With BPJS Kesehatan claims reaching IDR 201 trillion in 2025 and ongoing cases of alleged fraud at multiple hospitals, the legal construction of mens rea in upcoding fraud demands rigorous examination. Objective: This study analyzes why repeated patterns of coding errors that increase JKN claim values can be constructed as indicators of mens rea and formulates legal proof parameters to distinguish administrative errors from intentional fraud. Methods: This prescriptive normative juridical research employs a deductive syllogism method, in which the major premise comprises the doctrine of mens rea and anti-fraud regulations, the minor premise consists of upcoding fact patterns derived from empirical case analysis, and the conclusion presents a prescriptive legal construct. Results: The study produces a six-indicator model for mens rea assessment and a graduated liability framework distinguishing human error, culpa, dolus eventualis, and opzet in JKN claim coding. Conclusion: Repeated upcoding, when accompanied by clinical-documentary nonconformity and institutional awareness of prior warnings, constitutes sufficient inferential evidence for constructing mens rea under Indonesian criminal law.